Community Social Communication of Kuta Village in Maintaining Wisdom Values - Turmudi, Hamzah (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2023)
Kampung Kuta is a community that still survives, carrying out traditions that are the legacy of its ancestors, starting from belief systems, values, culture, livelihoods, and knowledge systems. This study aims to obtain an overview of the messages of local wisdom values and communication patterns of the Indigenous People of Kampung Kuta in maintaining local wisdom values, which have been a guide in their daily lives. This study uses a constructive paradigm, qualitative approach, and descriptive analysis method. Observation, interviews and documentation do data collection. The results of the study show that, first, the messages of the local wisdom of the Kuta village community are conveyed through various aspects of daily life; second, the communication patterns of the Kuta villagers are built persuasively, and they also try to find out how the communication can be received and carried out well by the internal community as well as guests or visitors from outside. Then residents and visitors must communicate according to the pattern that applies to the indigenous people of the village of Kuta. Socio-cultural messages will be more effective when delivered with a persuasive approach